Ready, Steady, Green: Examining the Effectiveness of External Policies to Enhance the Adoption of Eco‐Friendly Innovations. Issue 3 (19th January 2017) - Heidenreich, Sven; Spieth, Patrick; Petschnig, Martin
Abstract : The development and adoption of eco‐friendly innovations needs to be enhanced to reduce emissions caused by industry and transportation. Companies have been heavily investing in technologies and manufacturing processes to improve the development of eco‐friendly innovations such as alternative fuel vehicles (AFVs). While the long‐term viability of AFVs will be determined by consumer demand, only few consumers are willing to adopt these eco‐friendly innovations. To increase the diffusion of AFVs, it appears crucial to reach a critical mass of adopters and thus the point at which an innovation spreads exponentially through a target market. In this respect, previous research points to the importance of using external policies to turn the early majority into early adopters, which are primarily distinguished by their extent of innovativeness. However, diffusion theory suggests that consumer innovativeness as an innate trait is fairly stable over time and is thus not externally changeable. Yet, external measures might still be effective in strengthening effects of consumer innovativeness, turning the early and perhaps also the late majority into early adopters. Unfortunately, current research on consumer adoption behavior in general and on AFV adoption still lacks studies of the effectiveness of different external measures to turn potential adopters into early adopters by fostering positive effects of consumer innovativeness. This article addresses this shortcoming by empirically analyzing data from 1080 consumer evaluations in the domain of AFVs. Results from structural equation modeling confirm that AFV adoption relates positively to consumer innovativeness and that this effect can be intensified by providing external policies such as infrastructure, incentives, and communication policies.